TANADASHIP Techniques on Anxiety Level in Non-Intubation Covid 19 Patients at Wisma Atlit - Novia Wulansari; Diana Irawati; Tria Astika Endah Permatasari (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
A new type of virus in humans that emerged in 2019 and caused the 6th pandemic event in world history since 1918 is the novel coronavirus or currently known as COVID-19. The increasing prevalence of confirmed cases of COVID-19 in Indonesia has been recorded until now there are 1,191,990 confirmed cases, and the average addition of cases per day is 18.1%. This research is about giving deep breathing, spiritual, and five-finger hypnosis (TANADASHIP) techniques to anxiety levels in COVID 19 patients at Wisma Atlet Jakarta Hospital. To find out the decrease in anxiety levels in covid 19 patients who received the deep breath, spiritual, and five-finger hypnosis (TANADASHIP) intervention. This study uses a quasi-experimental design. The sampling technique used purposive sampling. The population in this study amounted to 68 were confirmed COVID-19 patients who were treated in the COVID-19 isolation room at the Wisma Atlet Jakarta Hospital. Data analysis includes normality test, univariate analysis and bivariate analysis. This research has passed the ethical test with 0915/7.9-UMJ/VIII/2021. There is a significant difference between the level of anxiety in COVID-19 patients who were given deep breathing, spiritual, and five-finger hypnosis (TANADASHIP) techniques.